RAMADAN-ASSOCIATED CIRCADIAN CENSUS VARIATION IN A BUSY MIDDLE EASTERN EMERGENCY DEPARTMENT - Thomas, Sarah Alice; Bashir, Khalid; Jenkins, Dominic William; Pathan, Sameer Abdussattar; Thomas, Stephen Hodges (Journal of Ayub Medical College Abbottabad, 2019)
Objectives: An important goal for the Emergency Department operations is planning for changes in patient volume and assuring staffing accordingly. We hypothesized that understanding the Emergency Department census changes during the month-long Ramadan holiday each year could facilitate operations planning for Emergency Department’s serving a largely Muslim population. Methodology:This was an observational study conducted at an academic center, over 83 weeks of analysis that included two Ramadan months (those occurring during 2016 and 2017). The data was from an electronic medical record that records presentation time as well as age, sex, nationality, and acuity. Chi-square and median-differences testing (p < .05 defining significance) were used to compare overall patient characteristics between cases seen during Ramadan vs. non-Ramadan. Results: For the 83 study weeks, the Emergency Department volume was 689,140 (annualized volume 431,750). Graphic depiction of weekly census showed Ramadan-associated census impact varied markedly over the course of a day’s 24 hours. Statistically significant hourly census increase (of up to 83%) or decrease (of as much as 50%) were identified for 21 of 24 hours of the day. Ramadan was not associated with change in patient age or proportion of high-acuity cases. However, it was associated with increase in proportion of males, pediatrics, and Qatari national’s patient visits. Conclusions: As compared to non-Ramadan baseline, Ramadan was associated with substantial changes in overall census and in proportions of various patient subgroups. Therefore, Emergency Department’s serving large Muslim population should undertake studying major operations changes that can be expected for the month. Background: An important goal for the Emergency Department operations is planning for changes in patient volume and assuring staffing accordingly. We hypothesized that understanding the Emergency Department census changes during the month-long Ramadan holiday each year could facilitate operations planning for Emergency Department’s serving a largely Muslim population. Methods: This was an observational study conducted at an academic centre, over 83 weeks of analysis that included two Ramadan months (those occurring during 2016 and 2017). The data was from an electronic medical record that records presentation time as well as age, sex, nationality, and acuity. Chi-square and median-differences testing (p<.05 defining significance) were used to compare overall patient characteristics between cases seen during Ramadan vs. non-Ramadan. Results: For the 83 study weeks, the Emergency Department volume was 689,140 (annualized volume 431,750). Graphic depiction of weekly census showed Ramadan-associated census impact varied markedly over the course of a day’s 24 hours. Statistically significant hourly census increase (of up to 83%) or decrease (of as much as 50%) were identified for 21 of 24 hours of the day. Ramadan was not associated with change in patient age or proportion of high-acuity cases. However, it was associated with increase in proportion of males, paediatrics, and Qatari national’s patient visits. Conclusions: As compared to non-Ramadan baseline, Ramadan was associated with substantial changes in overall census and in proportions of various patient subgroups. Therefore, Emergency Department’s serving large Muslim population should undertake studying major operations changes that can be expected for the month. Keywords: Ramadan; Emergency department operations; Emergency department